Evaluation and Grading of Students' Writing: Holistic and Analytic Scoring Rubrics - Al-Ghazo, Abeer; Ta'amneh, Issam (Journal for the Study of English Linguistics, 2021)
The paper tries to investigate the most preferable writing scoring rubrics when assessing students' writing assignments and to find the dimensions that teachers who teach English as a foreign language (EFL) emphasize when scoring EFL writing summaries. Thirty male and female Jordanian EFL teachers who teach English in both basic and secondary schools were participated to collect the necessary data. To conduct the study, a questionnaire consisting of twenty-seven items was prepared and disturbed by the researchers to suit the purpose of the study. In order to analyze the participants' respondents in the questionnaire, the researchers calculate Percentages, Means, Standard Deviations. The results revealed that there is a high interest in using analytic scoring rubrics to correct their students’ writing. The total mean reached 3.27 with standard deviation (0.65) by high agreement degree. Moreover, the results also highlight the importance of using scoring rubrics as precise and effective methods to assess the learners’ writing performance.